2005
DOI: 10.1158/0008-5472.can-05-0623
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6, Secreted by Human Ovarian Carcinoma Cells, Is a Potent Proangiogenic Cytokine

Abstract: Angiogenesis, a key rate-limiting step in the growth and dissemination of malignant tumors, is regulated by the balance between positive and negative effectors. Recent studies indicate that the pleiotropic cytokine interleukin-6 (IL-6) may contribute to the vascularization of some tumors by disrupting the equilibrium between positive and negative angiogenic regulatory molecules. We determined whether IL-6 participates in the angiogenesis observed during the progression of ovarian carcinoma. We measured IL-6 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
208
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 295 publications
(223 citation statements)
references
References 30 publications
9
208
1
2
Order By: Relevance
“…Several lines of evidence have demonstrated that IL-6 production and Stat3 activation may prevent cell death and lead to immunosuppression and drug resistance through upregulation of survival proteins in ovarian cancer [8,19,22,25]. Therefore, IL-6 and Stat3 proteins emerged as important targets for ovarian cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several lines of evidence have demonstrated that IL-6 production and Stat3 activation may prevent cell death and lead to immunosuppression and drug resistance through upregulation of survival proteins in ovarian cancer [8,19,22,25]. Therefore, IL-6 and Stat3 proteins emerged as important targets for ovarian cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is a progrowth, proangiogenic and anti-apoptotic cytokine that has been elevated in serum and ascites of patient with ovarian cancer as well as in culture supernatant of multi-drug resistant cell lines [8,[19][20][21]. In many tumors, elevated IL-6 levels in the serum is predictive of poor clinical outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interleukin-6 (IL-6) is another important molecule in tumor progression and angiogenesis [48]. IL-6 has been shown to be secreted by ovarian cancer cells and to enhance tumor cell proliferation and migration in vitro [49,50].…”
Section: Angiogenesismentioning
confidence: 99%
“…IL-6 has been shown to be secreted by ovarian cancer cells and to enhance tumor cell proliferation and migration in vitro [49,50]. Furthermore, IL-6 is a potent angiogenic cytokine in vivo as evidenced by gelfoam sponge assays, showing a significant increase in microvessel density in the IL-6 impregnated sponges compared to control [48]. Clinically, individuals experiencing chronic stress have been shown to exhibit elevated circulating levels of IL-6 [51].…”
Section: Angiogenesismentioning
confidence: 99%